2021
DOI: 10.1126/sciadv.abf7684
|View full text |Cite
|
Sign up to set email alerts
|

PHF8-promoted TOPBP1 demethylation drives ATR activation and preserves genome stability

Abstract: The checkpoint kinase ATR [ATM (ataxia-telangiectasia mutated) and rad3-related] is a master regulator of DNA damage response. Yet, how ATR activity is regulated remains to be investigated. We report here that histone demethylase PHF8 (plant homeodomain finger protein 8) plays a key role in ATR activation and replication stress response. Mechanistically, PHF8 interacts with and demethylates TOPBP1 (DNA topoisomerase 2-binding protein 1), an essential allosteric activator of ATR, under unperturbed conditions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Moreover, we performed single‐cell regulatory network inference and clustering (SCENIC) analysis to systemically infer TF‐driven regulons of each tumor cell subpopulation. As shown in Figure 5E and Table S6, HB1–Pro‐like1 cells were highly enriched of multiple MYC‐associated TF regulons (MYC/HMGA1/HMGA2/MXD1), HB1–Pro‐like2 cells were highly enriched of cell cycle‐associated TF regulons (MYBL1/MYBL2/E2F1/TFDP1), HB1–Pro‐like3 cells were highly enriched of cholangiocyte‐associated TF regulons (JUN/TFF3/KLF5),19,21 HB1–Pro‐like4 cells were moderately enriched of hepatocyte‐ and cell cycle‐associated TF regulons (HNF4A/MYBL2/E2F1/TFDP1), HB2–mesenchyme‐like cells were highly enriched of WNT‐ and mesenchymal cell‐associated TF regulons (CTNNB1/TCF3/TCF4/TCF7/TWIST1), HB3–hepatocyte‐like cells were highly enriched of hepatocyte‐associated TF regulons (HNF1A/HNF4A/ESR1), and HB4 cells were enriched of DNA damage repair‐associated TF regulons (IRF9/AR/PPARGC1A/PHF8) 22–25. The expression analysis further confirmed a correlation between TF regulon enrichment and transcript levels (Figure S9D).…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, we performed single‐cell regulatory network inference and clustering (SCENIC) analysis to systemically infer TF‐driven regulons of each tumor cell subpopulation. As shown in Figure 5E and Table S6, HB1–Pro‐like1 cells were highly enriched of multiple MYC‐associated TF regulons (MYC/HMGA1/HMGA2/MXD1), HB1–Pro‐like2 cells were highly enriched of cell cycle‐associated TF regulons (MYBL1/MYBL2/E2F1/TFDP1), HB1–Pro‐like3 cells were highly enriched of cholangiocyte‐associated TF regulons (JUN/TFF3/KLF5),19,21 HB1–Pro‐like4 cells were moderately enriched of hepatocyte‐ and cell cycle‐associated TF regulons (HNF4A/MYBL2/E2F1/TFDP1), HB2–mesenchyme‐like cells were highly enriched of WNT‐ and mesenchymal cell‐associated TF regulons (CTNNB1/TCF3/TCF4/TCF7/TWIST1), HB3–hepatocyte‐like cells were highly enriched of hepatocyte‐associated TF regulons (HNF1A/HNF4A/ESR1), and HB4 cells were enriched of DNA damage repair‐associated TF regulons (IRF9/AR/PPARGC1A/PHF8) 22–25. The expression analysis further confirmed a correlation between TF regulon enrichment and transcript levels (Figure S9D).…”
Section: Resultsmentioning
confidence: 95%
“…Replication stress results in KDM7B phosphorylation and dissociation from topoisomerase IIβbinding protein 1 (TOPBP1). Consequently, hypomethylated TOPBP1 facilitates RADiation-sensitive 9-binding to chromatin to fully activate ATR and thus safeguard the genome and protect cells against replication stress (Feng et al, 2020;Ma et al, 2021). Although many studies have observed the role of KDM7B in transcription silencing, further studies are needed to elaborate on the role of KDM7B in the DDR.…”
Section: Histone H4 Lysine20 Demethylationmentioning
confidence: 99%
“…10 Recent research has also discovered that Topbp1 can reduce methylation levels by binding to plant homeodomain finger protein 8 (PHF8) through the C-terminal BRCT7/8. 11 PHF8 is a histone demethylase that recognizes histone H3 lysine 4 (H3K4) methylation marks through its N-terminal PHD domain. Additionally, its C-terminal Jumonji C domain facilitates demethylation reactions of various lysine residues on histones.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At this stage, low-methylated Topbp1 is recruited and bound by RAD9. 11 Eventually, ATR binds to Topbp1, resulting in the formation of a complete complex and activation of ATR (Figure 1). 18,19 Under physiological conditions, PHF8 undergoes phosphorylation and dissociates from Topbp1 in response to signals from cellular replication stress.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation